Sypialnie Wrocławia w X-XII wieku - Kaźmierczyk, Józef (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
In the colloquial language of today the term „bedroom" denotes a place primarily used for sleeping. Its origins go back in Wroclaw at latest to the turn of the 10th/11th centuries or to the early 11th century coeval with the origin of the town. A room of that period, divided into two parts by a wall of wattle, is used here as a point of reference. The bedroom may have been at least 2.20 m long with the floor space of 1.7 m2 to 4 m2. A heap of birch bark or an oblong box may have served for sleeping. Another sleeping accomodation in Wroclaw of the 11th and 12th centuries was a board of a size adequate for the human body. Two or more boards placed side by side are regarded as so many beds for the whole family. Children slept in pens. In the poorest houses people slept on matted straw. Sleeping on benches was quite popular in the Early Middle Ages. In the 10th and in the next two centuries sanitary conditions of resting and sleeping (excluding bedding) on Ostrów Tumski in Wrocław seem to have been distinctly differentiated, representing at least three levels. This was presumably due to the differences in wealth and status of the population living there in the early part of the 10th century. A room with a bed isolated from the common room at the turn of the 10th/l1th centuries was here a crowning achievement. Beds for adults and children placed side by side indicate simpler needs. They either formed a block possibly enclosed by a curtain of soft fabric or ran along the wall. The poorest beds were made on the floor on a bundle of straw or moss. Their permanent location in a particular part of the room does not seem always probable.